Response of Arabidopsis to Iron Deficiency Stress as Revealed by Microarray Analysis - Thimm, Oliver (American Society of Plant Physiologists, 2001)
Gene expression in response to Fe deficiency was analyzed in Arabidopsis roots and shoots through the use of a cDNA collection representing at least 6,000 individual gene sequences. Arabidopsis seedlings were grown 1, 3, and 7 d in the absence of Fe, and gene expression in roots and shoots was investigated. Following confirmation of data and normalization methods, expression of several sequences encoding enzymes known to be affected by Fe deficiency was investigated by microarray analysis. Confirmation of literature reports, particularly for changes in enzyme activity, was not always possible, but changes in gene expression could be confirmed. An expression analysis of genes in glycolysis, the tricarboxylic acid cycle, and oxidative pentose phosphate pathway revealed an induction of several enzymes within 3 d of Fe-deficient growth, indicating an increase in respiration in response to Fe deficiency. In roots, transcription of sequences corresponding to enzymes of anaerobic respiration was also induced, whereas in shoots, the induction of several genes in gluconeogenesis, starch degradation, and phloem loading was observed. Thus, it seemed likely that the energy demand in roots required for the Fe deficiency response exceeded the capacity of oxidative phosphorylation, and an increase in carbon import and anaerobic respiration were required to maintain metabolism.